Thicker Shell Eggs with Enriched N-3 Polyunsaturated Fatty Acids and Lower Yolk Cholesterol Contents, as Affected by Dietary Nettle (Urtica cannabina) Supplementation in Laying Hens - Jize Zhang; Ta Na; Yanmei Jin; Xiaoqing Zhang; Hui Qu; Qian Zhang (Animals, 2020)
The nettle Urticacannabina (U.cannabina) is not only a functional edible food for humans but also a potential alternative feed resource for poultry, providing protein, fatty acids, vitamins, and minerals. The present study was conducted to evaluate the effects of dietary U.cannabina on the production of high-quality eggs with enriched n-3 polyunsaturated fatty acids (PUFA) and lower cholesterol contents. One hundred and twenty laying hens were assigned to three groups [control, 15% alfalfa meal supplementation (TRTA), and 15% U.cannabina supplementation (TRTU)]. The results showed that the feed intake, yolk color, and shell thickness were increased (p < 0.05) in the U.cannabina group. Moreover, cholesterol contents of the yolk and serum were lower in the U.cannabina group (p < 0.05). The total n-3 PUFA concentration in the yolk was increased while the ratio of n-6/n-3 was reduced in the U.cannabina group (p < 0.01). In conclusion, the dietary inclusion of U.cannabina increased shell thickness, yolk n-3 PUFA levels, and yolk color, and reduced cholesterol contents of the yolk and serum without any negative impacts on health or laying performance.